PENGARUH PENERAPAN METODE KOOPERATIF TIPE PROBING PROMTING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 RAO SELATAN TAHUN PELAJARAN 2012/2013 - Purnama, Ira; Rismen, Sefna; Husna, Husna (Pendidikan Matematika, 2013)
The background of this research is the comprehension of math concepts class VIII SMPN1 South Rao is still low. This study aims to determine whether students comprehension of mathematical concepts with the application of cooperative methods Probing promting better than students comprehension of mathematical concepts with conventional teaching class VIII SMPN1 Rao Selatan.Jenis this research is experimental research design Randomized Only Control Group Design. The population in this study were all eighth grade students enrolled in the school year 2012/2013. The sampling technique was randomly selected as the class VIII2 VIII1 experimental class and the control class. The instrument used in this study is the final test in the form of essays with a reliability test was 0.89. The data analisys which ttest = 1.74 is greather than ttabel = 1.654it was concluded that the students comprehension of mathematical concepts that apply cooperative learning methods Probing promting better than conventional learning in class VIII SMPN1 South Rao.